Integrating English and Digital Literacy for Older Adults - Ochoa Siguencia, Luis (International Journal of Advanced Corporate Learning (iJAC), 2025)
This paper investigates how best to integrate English and digital literacy education for older adults to promote their digital social inclusion. The research of the ERASMUS+ project Coll-Oya focuses on the learning needs of adults aged 55 and older from Tarragona-Spain, Silesia-Poland, and Adana-Türkiye. These participants make up part of a divergent group that, though still active in life, are not digital natives. Most of them have insufficient knowledge of digital tools and the English language to be able to handle new technologies. This project thus responds to these gaps since it seeks to equip participants with both English language skills and digital literacy through content-based instruction combined with practical applications in reallife activities such as online shopping, ticket booking, and engaging in digital communication. The study explores participants’ digital awareness, language proficiency, and collaborative learning experiences with younger generations. A mixed-methods approach involving 204 participants completing an online survey and 45 interviews explores their preferences and challenges in acquiring language and digital skills. The main findings show that tailored learning opportunities increase engagement and motivation among older learners and empower them, instilling a sense of hope and inspiration. Intergenerational collaboration creates a supportive learning environment. Participants reported feeling more confident using technology and improving their English language skills through the joint teaching initiatives. The paper suggests that integrating English and digital literacy training could offer an opportunity to empower the active contribution and social inclusion of those over age 55 in the increasingly digital world. These findings provide pragmatic insights into how the digital competencies of older adults and their language proficiency can be supported in intergenerational learning, thus practically presenting strategies to educators, policymakers, and other stakeholders involved in adult education and digital literacy.